2007
DOI: 10.1210/en.2006-1296
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Voltage-Gated K+and Ca2+Channels and SolubleN-Ethylmaleimide-Sensitive Factor Attachment Protein Receptor Proteins to Cholesterol-Rich Lipid Rafts in Pancreatic α-Cells: Effects on Glucagon Stimulus-Secretion Coupling

Abstract: Pancreatic alpha-cells secrete glucagon in response to low glucose to counter insulin actions, thereby maintaining glucose homeostasis. The molecular basis of alpha-cell stimulus-secretion coupling has not been fully elucidated. We investigated the expression of voltage-gated K(+) (K(V)) and Ca(2+) (Ca(V)) channels, and soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) proteins in pancreatic alpha-cells and examined their targeting to specialized cholesterol-rich lipid rafts. In alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 48 publications
2
41
1
Order By: Relevance
“…However, our observation that Kv2.1/Kv2.2 and BK account for the majority of Kv current in alpha cells suggests that Kv3 channels play only a minor role. Finally, Kv4.3 has been suggested to contribute a rapidly inactivating TEAinsensitive Kv current in mouse alpha cells [3,6,19]. We did not detect such a current in our preparation, and the Kv4.3 inhibitor phrixotoxin had no effect on alpha cell Kv currents in our hands.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…However, our observation that Kv2.1/Kv2.2 and BK account for the majority of Kv current in alpha cells suggests that Kv3 channels play only a minor role. Finally, Kv4.3 has been suggested to contribute a rapidly inactivating TEAinsensitive Kv current in mouse alpha cells [3,6,19]. We did not detect such a current in our preparation, and the Kv4.3 inhibitor phrixotoxin had no effect on alpha cell Kv currents in our hands.…”
Section: Discussioncontrasting
confidence: 55%
“…This discrepancy may relate to differences in cell preparation, cell identification or recording conditions. Previous studies examined alpha cells identified electrophysiologically in intact islets [3] or green fluorescent protein (GFP)-negative single cells from mouse insulin promoter-GFP islets [6,19]. The present study examined isolated cells, which were identified postexperimentation by glucagon immunostaining.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…SNAP-25 and syntaxin 1A have been demonstrated to be present in glucagon secreting cells [38] but to our knowledge no study has earlier addressed the temporal aspects of these proteins in relation to the different functional pools. Here we have used confocal microscopy to investigate glucose-dependent localization of SNAP-25 and syntaxin 1A.…”
Section: Introductionmentioning
confidence: 99%